1999
DOI: 10.1091/mbc.10.2.417
|View full text |Cite
|
Sign up to set email alerts
|

Eps15 Is Recruited to the Plasma Membrane upon Epidermal Growth Factor Receptor Activation and Localizes to Components of the Endocytic Pathway during Receptor Internalization

Abstract: Eps15 is a substrate for the tyrosine kinase of the epidermal growth factor receptor (EGFR) and is characterized by the presence of a novel protein:protein interaction domain, the EH domain. Eps15 also stably binds the clathrin adaptor protein complex AP-2. Previous work demonstrated an essential role for eps15 in receptor-mediated endocytosis. In this study we show that, upon activation of the EGFR kinase, eps15 undergoes dramatic relocalization consisting of 1) initial relocalization to the plasma membrane a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
103
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 44 publications
(77 reference statements)
10
103
2
Order By: Relevance
“…However, our current data do not establish that cargo itself needs to be ubiquitinated. Grb2 and Cbl were interestingly found to specifically localize to the rim of EGFR-positive clathrin coats in the same manner as previously reported for Eps15 (Torrisi et al, 1999;Stang et al, 2000). We have further demonstrated that also hSpry2 localizes to the rim of coated pits in transfected cells.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, our current data do not establish that cargo itself needs to be ubiquitinated. Grb2 and Cbl were interestingly found to specifically localize to the rim of EGFR-positive clathrin coats in the same manner as previously reported for Eps15 (Torrisi et al, 1999;Stang et al, 2000). We have further demonstrated that also hSpry2 localizes to the rim of coated pits in transfected cells.…”
Section: Discussionsupporting
confidence: 87%
“…It was reported that Grb2 colocalized with the ␤2 subunit of AP-2 and EGF upon incubation of PAE cells with EGF for 1 h at 4°C . We have previously demonstrated that the EGFR colocalizes with Cbl at the plasma membrane under similar conditions (Longva et al, 2002), and it has also been shown that Eps15 is recruited to the plasma membrane when cells are incubated with EGF on ice (Torrisi et al, 1999). As expected, we found by immunofluorescence and confocal microscopy that incubation of Hep2 cells with EGF on ice for 60 min recruited Grb2, Cbl, and Eps15 to the plasma membrane ( Figure 4A).…”
Section: Grb2 and Cbl Localize At The Rim Of Clathrin-coated Pits In supporting
confidence: 84%
“…The clathrin-dependent pathway has been shown to be the primary pathway for ligand-induced BCR endocytosis, and raft structures appear to be required for efficient phosphorylation of clathrin heavy chain [21,33]. Tyrosine-phosphorylation of clathrin heavy chain is induced by an SRC-type protein kinase in response to stimulation of various receptor types, and the level of phosphorylation correlates with the rate of receptor internalization [21,[34][35][36][37]. Our data support a requirement for phosphorylation of clathrin heavy chain as well as for that of other endocytosis-related factors in BCR internalization.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR pathway substrate (Eps) 15 and epsin1 are members of a family of ubiquitin-interacting motif (UIM) containing proteins that govern the early steps of EGFR endocytosis [30][31][32] . Therefore, we investigated whether the loss of PHD3 affects the recruitment of Eps15 and epsin1 to EGFR.…”
Section: Phd3 Interacts With Egfr and Regulates Its Internalizationmentioning
confidence: 99%